Baitul Rahmah: a Final Evolution of The Malay Classical Style Amidst Change - Noorhanita Abdul Majid; Puteri Shireen Jahn Kassim; Tengku Anis Qarihah Binti Raja Abdul Kadir; Abdul Razak Bin Sapian; Abu Dzar Bin Samsudin (Cultural Syndrome, 2020)
The paper highlights the significance and position of the Baitul Rahmah, an early 20th-century mansion in Kuala Kangsar, Perak, Malaysia, as a key milestone of stylistic  evolvement of local vernacular architecture. Its form embodies, a typological variation  at a time of growing Colonial imperialism, while its grammar and language refers to early modern  stylistic expression reflecting the fundamental principles of indigenous architecture. The Baitul Rahmah brings to light how a final evolution and epitome of  the vernacular projects an identity as a cosmopolitan manifestation.  Its internal ornamentation recalls the stylized forms of local motifs and reflect a form of control and minimalism; i.e. an ‘ornamental decorum’. Its wood-carved expressions seem stylised into increasing ‘modernised’ simplication and  modularity, while  its masonry- timber structure reflect the identity of hybridity  in architecture which symbolise the tensions of local communities as they step into the 1900s into a global context.